Women reduced the sex difference in open-water ultra-distance swimming La Traversée Internationale du Lac St-Jean, 1955-2012 - Rüst, C. A.; Knechtle, B.; Rosemann, T.; Romuald Lepers, R. (Applied Physiology, Nutrition, and Metabolism, 2014)
In La Traversée Internationale du Lac St-Jean, held between 1955 and 2012 in Canada, the fastest women (r2 = 0.61, p < 0.0001) and men (r2 = 0.66, p < 0.0001) improved swimming speed over the years but the sex difference remained unchanged at 8.8% ± 5.6% (r2 = 0.069, p = 0.065). Annually, for the 3 fastest swimmers, both women (r2 = 0.53, p < 0.0001) and men (r2 = 0.71, p < 0.0001) improved swimming speed between 1973 and 2012 and the sex difference decreased (r2 = 0.29, p = 0.0016) from 14.4% ± 11.0% (1973) to 3.7% ± 1.4% (2012).